2011
DOI: 10.1177/0142723710393101
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in using nominal number inflections in Kuwaiti Arabic

Abstract: The acquisition of dual and plural nominal marking was examined. Forty-four Kuwaiti Arabic-speaking children aged 4-9 years were presented with a set of pictured stimuli of real and nonsense words and were asked to provide the plural and dual form. The results showed that Feminine Sound Plural (FSP) was used early on and more frequently than the Masculine Sound Plural (MSP) and the Broken Plural (BP). FSP was noticeably employed as the default form by younger children before differentiation gained ground, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 22 publications
9
15
0
Order By: Relevance
“…Moreover, the children, especially the younger ones, showed a tendency to use sound feminine plurals instead of sound masculine and broken plurals. Similar patterns were reported in studies on other Arabic dialects, such as Jordanian (Daana, ), Kuwaiti (Aljenaie, Abdalla, & Farghal, ), and Egyptian (Omar, ). Most of these studies suggest that sound feminine plurals seem to act as the default category that is acquired earlier than other forms and often extended to the expected masculine and broken plural forms.…”
Section: Studies On the Acquisition Of Arabic Plural Morphologysupporting
confidence: 87%
“…Moreover, the children, especially the younger ones, showed a tendency to use sound feminine plurals instead of sound masculine and broken plurals. Similar patterns were reported in studies on other Arabic dialects, such as Jordanian (Daana, ), Kuwaiti (Aljenaie, Abdalla, & Farghal, ), and Egyptian (Omar, ). Most of these studies suggest that sound feminine plurals seem to act as the default category that is acquired earlier than other forms and often extended to the expected masculine and broken plural forms.…”
Section: Studies On the Acquisition Of Arabic Plural Morphologysupporting
confidence: 87%
“…At age seven, the acquisition of the plural is still at around 90 percent accuracy compared to adults. Aljenaie, Abdalla, and Farghal (2011), who examined the development of noun number marking, dual and plural, by Kuwaiti Arabic-speaking children between the ages of four and nine years in an elicited production task, also found that correct FSP appeared more frequently than MSPs and BPs in Group 1 (four-to five-year-olds) and demonstrated near-ceiling effects in Group 2 (six-to seven-year-olds) and Group 3 (eight-to nine-year-olds). In contrast, the acquisition of the other two plural types (MSP and BP) increased in accuracy across age groups.…”
Section: Nominal Plural Morphology In Kuwaiti Arabicmentioning
confidence: 99%
“…Instead, DS children and young adults rely more on their environmental language input, for the plural number form is more used in JA than the dual number form. Hence, the dual number is acquired after the plural in DS, unlike in the typical children reported in Moawad ( 2006 ) and Aljenaie et al ( 2011 ), reflecting the sensitivity to the surrounding environment by individuals with DS. Thus, children and young adults with DS perform a considerable amount of dependency in using more social language (Martin et al, 2009 ).…”
Section: Discussionmentioning
confidence: 75%
“…The plural form is, however, considered as a weakness area in DS; it is the second most commonly and correctly used number after the default singular, as it is used to denote the dual number more than the typical dual form and the canonical plural form. This is the opposite of acquisition behaviour in typically developing children (Aljenaie et al, 2011 ). In addition, it is at variance with the argument that children with DS acquire the linguistic patterns at a similar phase to TDC children.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation